Effect of peripheral field loss on gait performance: a systematic review and meta-analysis - Jia, Shuwen; Bello, Umar Muhammad; Zhao, Mei; Lyu, Anqi; Wong, Ginny H. T.; Thompson, Benjamin; Cheong, Allen Ming Yan (Frontiers in Neuroscience, 2025)
BackgroundThe peripheral visual field provides essential environmental information for safe locomotion. Deficits in peripheral field can adversely affect gait performance and safety. This review aimed to consolidate current knowledge on the impact of peripheral field loss on gait and to identify the key parameters for gait assessment.MethodsA comprehensive systematic search was conducted across AMED, CINAHL, PubMed, Scopus, and Web of Science databases, supplemented by a manual search on Google Scholar, covering the period up to November 2023. Eligible studies examining the relationship between peripheral field loss and gait performance were summarized and methodologically assessed using the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) quality rating tool. Meta-analysis was conducted using the Comprehensive Meta-analysis (CMA) software.ResultsThe review included 23 studies with a total of 3,085 participants. The average STROBE score was 19, ranging from 15 to 21. Walking speed was the most frequently assessed gait parameter, with peripheral field loss significantly associated with reduced walking speed (r = 0.40, p < 0.001). In addition, peripheral field loss correlated with an increased number of collisions, indicating compromised mobility safety. Moreover, alterations in spatiotemporal gait parameters, such as stride length and cadence, were also linked to peripheral field loss.ConclusionPeripheral field loss is significantly associated with reduced walking speeds, altered gait characteristics, and impaired mobility safety during locomotion. Future research should adopt a standardized set of gait and mobility metrics to enhance cross-study comparisons among diverse patient populations.Systematic Review RegistrationCRD42022297071.